Photoperiod and Melatonin Supplementation: Variable Effects on the Quality of Chilled Dog Semen - Mitjana, Olga; Ausejo, Raquel; Mendoza, Noelia; Miguel, Joaquin; Tejedor, Maria Teresa; Garrido, Ana Maria; Falceto, Maria Victoria (Frontiers in Veterinary Science, 2022)
The addition of melatonin in seminal extenders due to its antioxidant properties and its beneficial role in sperm preservation has been previously described, especially in seasonal species. The aim of this study was to study a potential seasonal effect based on photoperiod duration when adding a physiological concentration of melatonin in the canine ejaculate. A total of 24 ejaculates were obtained from 10 healthy dogs during the increasing photoperiod (from December 21 to June 21), whereas 12 ejaculates were collected from five healthy individuals during the decreasing photoperiod (from June 22 to December 20). Each ejaculate was separated into two aliquots, and one of them remained as a control, whereas melatonin (100 pM) was added to the other one (C and M treatment groups, respectively). Diluted semen was refrigerated at 5°C. On days 0, 1, 2, 3, and 6, sperm motility analyses were performed using a CASA system and hypoosmotic swelling test (HOST), osmotic resistance test (ORT), and flow cytometry analysis. No effect of melatonin on motility was detected in either photoperiod. Negative effects of melatonin were found for acrosomal defects, apoptosis, and viability in the decreasing photoperiod. The addition of melatonin to sperm in the decreasing photoperiod could create such a high level that it would cause the described negative effects. We found a beneficial effect of melatonin in the increasing photoperiod on acrosomal defects and apoptosis during 0–6 days. Melatonin treatment also increased viability in the short term (days 1 and 2) for both photoperiods. Also, melatonin can provide certain beneficial effects on mitochondrial activity in the medium term (days 2 and 3) in the decreasing photoperiod.